Trashducation / Badrul Emran Badrul Hisham … [et al.] - Badrul Hisham, Badrul Emran; Hamzah, Muhammad Ghazali; Syed Alw, Sharifah Nur Najiah Najela; Mohamad Shah, Nurul Anis Faizah; Nazri, Nur'syamimi Asyhikin (Division of Research and Industry Linkages, 2017)
We would like to introduce the product that we invented that functions in educating primary school students on the importance in sustaining the environment. People nowadays are not aware of the importance in taking care of the environment. For example, it seems to be normal for them to simply litter even though there is a bin just near them. Thus, we plan to educate our future generation In keeping the environment clean and safe for them to reside in. However, how do we sustain the environment? The function of this invention is by using psychology as well as some engineering. The machine is engineered to accept any trash that is given by it through a funnel in which it will collect the trash in a specific compartment inside of it. In return, users will receive a reward for delivering the trash, which is why understanding the human nature and the reward system is important. In the scope of primary schools, the rewards would be stickers to be used in sticker cards that teachers will hold on to. Students who complete a whole card worth of stickers can receive awards such as drinks, a free meal at the cafeteria or even receive merit for being environmentally aware. Through simple reward systems, children will be encouraged to throw away their litter in these environmentally friendly bins. With this machine, it will provide higher chances of an environmentally aware society by educating children in sustaining the environment. Further development of this machine could lead to awareness in larger scopes of the community, placing it in public parks or other public facilities. With this machine, it can create a cleaner environment around us as well as educating a more civilized society for a better future.